Transported Art:: 19th-Century Italian Sculptures Across Continents and Cultures - Bochicchio, Luca (Material Culture Review)

(untitled) (National Museums of Canada, 2012)
Abstract The international identity of 19th-century sculpture has been neglected for several years, and, as a result, artistic literature and research have almost completely ignored the fact that most 19th-century Italian sculpture is now spread all over the world. The purpose of this essay is to illustrate and document peculiar aspects of the diffusion of Italian sculpture in America between the mid-19th and early 20th century. Along with the flux of artwork, materials, and Italian sculptors to the Americas, over the decades straddling these two centuries there was an inverse movement of American artists (interested in Italian sculpture) to Rome, Florence, Genoa, Naples, and so on. Thanks to that double exchange, Italian sculpture became a strong, recognized influence worldwide. The aim of this paper is to establish an interdisciplinary context for sculpture, clarifying the connections with social, economic, and cultural factors.